Mangrove Conservation and Social-Ecological Resilience in a Community-Based Coastal Landscape of Indonesia - Agung Ardiyansah; Ghanishta Seeburrun; Shannon M Lambert (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the evolution of community-based mangrove conservation in Wringinputih Village, Indonesia, from the implementation of the Cofish Project to the present. It also aims to develop a social-ecological framework for future mangrove management that supports ecosystem restoration, biodiversity conservation, coastal landscape resilience, and sustainable community livelihoods. Methodology: This study employed a qualitative case study approach. Data were collected through field observations, in-depth interviews, document analysis, and source triangulation. Informants included village authorities, fisheries officers, Perhutani representatives, fisher groups, and aquaculture farmers. Environmental measurements utilized a pH meter, thermometer, hand refractometer, GPS, and digital camera. Data were analyzed using the Miles and Huberman interactive model. Main Findings: Mangrove conservation in Wringinputih Village evolved from ecosystem degradation caused by aquaculture expansion toward a community-based restoration model supported by multi-stakeholder collaboration. Continuous rehabilitation activities increased mangrove cover, improved habitat quality, enhanced biodiversity conservation, strengthened coastal protection functions, and supported fisheries resources. The proposed social-ecological framework highlights the integration of ecosystem restoration, community participation, institutional collaboration, environmental education, and sustainable livelihood development to strengthen coastal landscape resilience. Novelty/Originality of this study: This study provides a comprehensive reconstruction of mangrove conservation history from the Cofish Project period to the present and integrates the findings into a social-ecological resilience framework for coastal landscape management. Unlike previous studies focusing primarily on restoration outcomes or governance mechanisms, this research demonstrates how ecosystem recovery, biodiversity conservation, stakeholder collaboration, and community participation interact to support long-term mangrove conservation and landscape resilience.